Critical Speed Analysis of Sliding Bearing Rotor System Based On ANSYS. Issue 1 (August 2021) - Ming, Cheng; Xianbin, Teng; Qijiang, Yang; Songcheng, Pu; Yupeng, Wang; Yaodi, Lin; yachunyue, Zhou
Abstract: Sliding bearing rotor system plays an important role in rotating machinery, and its critical speed is a key index. In this paper, a sliding bearing rotor system is established, and the critical speed range is obtained by ANSYS Workbench software under different oil film stiffness, which provides guidance and basis for maintaining the stability of sliding bearing rotor system and avoiding resonance.